(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Tax collection is important in a modern market economy. The collection of taxes further expands the state’s ability to perform its function in the economy. The state of the level of tax collection makes it possible to determine the share of the shadow economy in the national economy